Velvet Bean (Mucuna pruriens) Productivity Undershade as a Feed Source - Rini Dwi Wahyuni; Hermanto Hermanto; Herni Sudarwati; Hanief Eko Sulistiyo (Politeknik Pembangunan Pertanian Malang, 2025)
This research, conducted under the shade of Albizia chinensis trees in Kediri, Indonesia, specifically tested whether pruning the beans at different growth stages (80, 100, or 120 days after planting) would boost productivity. Using a rigorous randomized block design across an 800 m² field, the study measured fresh and dry biomass, along with seed yields. The key finding was that the timing of pruning made no significant difference to the final yield. Instead, the most important factor was something more fundamental: access to water. Plots closer to a water source performed better, highlighting that basic resource availability is far more critical than pruning in this type of agroforestry system. While there were slight yield increases in some pruned plots, the results were too inconsistent to be statistically meaningful. Ultimately, the study confirms that velvet bean is a resilient crop, capable of growing with minimal inputs in shaded conditions. To truly optimize its production as a soybean alternative, farmers and agroforesters should focus on integrated strategies like improving irrigation or soil health, rather than investing effort in pruning. This work provides valuable insights for cultivating resilient legumes in challenging environments